2006
DOI: 10.1111/j.1469-8986.2006.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cognitive resources during sustained attention and working memory in 10‐year‐olds and adults

Abstract: We examined differences between 10-year-olds and young adults in resource recruitment and regulation during tasks of sustained attention and spatial working memory. We administered participants spatial 0- and 1-back tasks and used pupillary dilation as a measure of resource recruitment. Repeated administration of 0-back led to smaller pupillary dilations and greater response time (RT) variability, revealing a vigilance decrement. Effects of repeated administration of 0-back and differences between 0- and 1-bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 114 publications
(152 reference statements)
7
51
1
Order By: Relevance
“…Moment-by-moment changes in the temporal dynamics of control were assessed with the taskevoked pupillary response, a measure known to correlate with mental effort across ages and tasks (27) due to cortical modulation of the reticular formation (21). Notably, 8-year-olds showed increased delay-period effort, reflecting proactive maintenance of context in preparation for the subsequent response ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moment-by-moment changes in the temporal dynamics of control were assessed with the taskevoked pupillary response, a measure known to correlate with mental effort across ages and tasks (27) due to cortical modulation of the reticular formation (21). Notably, 8-year-olds showed increased delay-period effort, reflecting proactive maintenance of context in preparation for the subsequent response ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The present study confirms previous behavioural studies that found better response inhibition (fewer commission errors) and sustained attention performance 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 15 Sweeney, 2004) (Clark et al, 2006;Lin, Hsiao & Chen, 1999; though also see Karatekin, Marcus & Couperus, 2007). Greater response variability has been previously identified in clinical groups with frontal (Stuss et al, 2003) and fronto-striatal and fronto-parietal brain pathology (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Pupillary dilation can be affected by many environmental or participant-internal events (such as changes in lighting, emotional arousal, or the onset of stress; Beatty & Lucero-Wagoner, 2000;Goldwater, 1972;Hess, 1965;Hess, Seltzer, & Shlien, 1965;Loewenfeld, 1993). Importantly, however, changes in pupil size are also observed in relation to the demands elicited by cognitive tasks, and these changes have been shown to occur independently of other influences (Goldwater, 1972;Karatekin, Marcus, & Couperus, 2007). Such changes are generally observed by time-locking changes in pupil diameter to the onset of stimuli that elicit various cognitive processes, and thus are often referred to as task-evoked pupillary reflexes (Beatty, 1982;Kahneman & Beatty, 1966;Kahneman, Beatty, & Pollack, 1967).…”
Section: Event-related Potentials In the Study Of Receptive Vocabularmentioning
confidence: 99%